ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI HARMONISASI HUBUNGAN KEMITRAAN ANTARA PEKERJA DAN PENGUSAHA - Agus Ambarepto, Mugi Harsono & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2006)
ABSTRACT This research target is test the influence of worker perception about invitation regulation in laborship area, the existence of union labor and the existence of union to the harmonization relationship between worker and entrepreneur: study of at trade union manager/union labor. The first questioner is to measure the influence about understanding of regulation of invitation in laborship area. The second questioner is to measure the influence workers perception about the labor prosperity, the third questioner to measure the influence workers perception about the existence of union labor, and the fourth questioner is the harmonization between worker and entrepreneur by using alpha cronbach value equal to 0.6. in this research used by an appliance test the doubled linear analysis regression and also test the classic assumption. The result from this research is to show the existence of positive influence and significant of among the influence of worker perception about invitation regulation in laborship area. Labor prosperity and harmonization relationship between worker and entrepreneur by simultant Keywords: worker, labor prosperity, union labor, harmonization relationship